Limiting order of amino acid in Alfalfa Leaf Protein Concentrate (ALPC) for growing pigs - Hsu, A.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy-two crossbred pigs averaging 23.5 lb initially and 12 crossbred barrows averaging 31.5 lb initially were used to study the limiting order of amino acids in ALPC for growing pigs in a feeding trial and a nitrogen balance trial. The basal diet contained 20% ALPC, as the amino acids source, and dextrose, as the energy source. Pigs fed the basal diet supplemented with methionine gained faster (P<.05) and more efficiently than pigs fed the basal diet, indicating that methionine was the first limiting amino acid in ALPC. Adding L- isoleucine (.2%) in the presence of methionine and lysi1e improved daily gain and feed efficiency (P<.05). These results suggest that isoleucine is the second limiting amino acid. Results from the nitrogen balance trial showed that adding .3% DL-methionine increased nitrogen retention (P<.05), confirming the growth trial results that showed methionine to be the first limiting amino acid in ALPC for growing pigs.
Keywords: Swine; Amino acid; Alfalfa Leaf Protein Concentrate (ALPC); Growing pigs